PENGARUH KEPEMIMPINAN DAN DISIPLIN TERHADAP MOTIVASI KERJA SERTA DAMPAKNYA PADA KINERJA PEGAWAI RUMAH SAKIT UMUM BERSAUDARA KABUPATEN BUNGO - M. Alhudhori; Wahyu Aldino (J-MAS (Jurnal Manajemen dan Sains), 2017)
Leadership is one of the issues in the management is still quite interesting to be discussed today. The role of leadership is very strategically important for the achievement of the mission, vision and goals of an organization. One such way to impose discipline and provide motivation to work that can be perceived by employees.  The purpose of this study was to examine the influence of leadership, discipline, motivation and performance. The influence of leadership, discipline, motivation and performance of employees tested either directly or indirectly. To examine issues directly above the survey conducted by distributing questionnaires to employees in the General Hospital of the Brothers of Bungo. Data was analyzed by path analysis. The results of this study indicate that the leadership, discipline and work motivation influence simultaneously and partially on performance. Where is the leadership, discipline, motivation and performance of employees at the General Hospital Brothers, where are the good category, Discipline are in both categories, motivation and performance of employees are in both categories. The analysis tool in this research using descriptive method verification. Where the use of a range of scales, while in the verification using path analysis or path analysis.Key words : Leadership, Discipline, Motivation and Employee Performance